GE_GERICHTE P/19575/2022 vom 15. Februar 2024 - GE Cour de justice (2024)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;DROIT D'ÊTRE ENTENDU;MENACE(DROIT PÉNAL);CONTRAINTE(DROIT PÉNAL);INJURE | CPP.310; Cst; CP.180; CP.181; CP.177